Pan-Genome Analysis Reveals the Abundant Gene Presence/Absence Variations Among Different Varieties of Melon and Their Influence on Traits - Sun, Yang; Wang, Jing; Li, Yan; Jiang, Bin; Wang, Xu; Xu, Wen-Hui; Wang, Yu-Qing; Zhang, Pei-Tao; Zhang, Yong-Jun; Kong, Xiang-Dong (Frontiers in Plant Science, 2022)
Melon (Cucumismelo L.) is an important vegetable crop that has been subjected to domestication and improvement. Several varieties of melons with diverse phenotypes have been produced. In this study, we constructed a melon pangenome based on 297 accessions comprising 168 Mb novel sequences and 4,325 novel genes. Based on the results, there were abundant genetic variations among different melon groups, including 364 unfavourable genes in the IMP_A vs. LDR_A group, 46 favourable genes, and 295 unfavourable genes in the IMP_M vs. LDR_M group. The distribution of 709 resistance gene analogues (RGAs) was also characterized across 297 melon lines, of which 603 were core genes. Further, 106 genes were found to be variable, 55 of which were absent in the reference melon genome. Using gene presence/absence variation (PAV)-based GWAS, 13 gene PAVs associated with fruit length, fruit shape, and fruit width were identified, four of which were located in pan-genomic additional contigs.